Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

What happened with the smaller ones? First comprehensive taphonomic analysis of microvertebrates from the Late Pleistocene of Rancho La Brea (Los Angeles, USA) - Fernando J. Fernández; Claudia I. Montalvo; M. Dolores Marin‐Monfort; Renata Sostillo; Daiana G. Coll; Emily Lindsey; Karin A. Rice; Gary T. Takeuchi; Rodrigo L. Tomassini (Journal of Quaternary Science, 2025)
Rancho La Brea (RLB) in Los Angeles, USA, is an iconic fossil locality, owing to the high number and diversity of Quaternary vertebrate remains and their excellent preservation. More than a century of study, focused predominantly on large mammals, has provided valuable information along different lines of research, including taxonomy, taphonomy, isotopic ecology, functional morphology, and paleopathology. In order to develop a better understanding of the formation of this site, we conducted a taphonomic study of the microvertebrates, using samples from asphalt seeps dating to before the Last Glacial Maximum. The taphonomic evidence suggests that direct entrapment is the most plausible process to explain the primary accumulation of the thousands of microvertebrate remains. Based on the absence of digestive corrosion and feeding marks, low percentages of juvenile individuals, relative abundance patterns, and anatomical indices (postcranial elements vs. cranial elements and distal vs. proximal limb elements), the activity of predators/scavengers is ruled out as a primary process in producing the assemblages, although other processes, such as water transport of skeletal elements from nearby areas, could also have played a role in the formation of the deposits. The occurrence of successive entrapments and episodes of fluvial transportation, combined with post‐depositional internal movement within the seeps, would have given rise to the development of time‐averaged assemblages produced through a complex interplay of factors.

Validation of Markerless Motion Capture for Soldier Movement Patterns Assessment Under Varying Body-Borne Loads - Isabel Coll; Matthew P. Mavor; Thomas Karakolis; Ryan B. Graham; Allison L. Clouthier (Annals of Biomedical Engineering, 2025)

Current Trends and Future Directions in Urban Social Prescribing - J. S. Litt; L. Coll-Planas; A. L. Sachs; M. Masó Aguado; M. Howarth (Current Environmental Health Reports, 2023)

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis - Tim Whitfield; Thorsten Barnhofer; Rebecca Acabchuk; Avi Cohen; Michael Lee; Marco Schlosser; Eider M. Arenaza-Urquijo; Adriana Böttcher; Willoughby Britton; Nina Coll-Padros; Fabienne Collette; Gaël Chételat; et al. (Neuropsychology Review, 2022)
Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies ( n = 2,931) were included, of which 45 ( n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and subgroup analyses evaluated moderators. Pooling data across cognitive domains, the summary effect size for all studies favored MBPs over comparators and was small in magnitude ( g = 0.15; [0.05, 0.24]). Across subgroup analyses of individual cognitive domains/subdomains, MBPs outperformed comparators for executive function ( g = 0.15; [0.02, 0.27]) and working memory outcomes ( g = 0.23; [0.11, 0.36]) only. Subgroup analyses identified significant effects for studies of non-clinical samples, as well as for adults aged over 60. Across all studies, MBPs outperformed inactive, but not active comparators. Limitations include the primarily unclear within-study risk of bias (only a minority of studies were considered low risk), and that statistical constraints rendered some p -values unreliable. Together, results partially corroborate the hypothesized link between mindfulness practices and cognitive performance. This review was registered with PROSPERO [CRD42018100904].

Special issue on recent advances in zoophytophagous arthropods for agroecosystems sustainability - Alberto Urbaneja; Moshe Coll; Josep A. Jaques; Jose Eduardo Serrao; Dionysios Perdikis; Amy L. Roda (Journal of Pest Science, 2022)

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Twenty‐first‐century climate change impacts on marine animal biomass and ecosystem structure across ocean basins - Andrea Bryndum‐Buchholz; Derek P. Tittensor; Julia L. Blanchard; William W. L. Cheung; Marta Coll; Eric D. Galbraith; Simon Jennings; Olivier Maury; Heike K. Lotze (Global Change Biology, 2019)
Climate change effects on marine ecosystems include impacts on primary production, ocean temperature, species distributions, and abundance at local to global scales. These changes will significantly alter marine ecosystem structure and function with associated socio‐economic impacts on ecosystem services, marine fisheries, and fishery‐dependent societies. Yet how these changes may play out among ocean basins over the 21st century remains unclear, with most projections coming from single ecosystem models that do not adequately capture the range of model uncertainty. We address this by using six marine ecosystem models within the Fisheries and Marine Ecosystem Model Intercomparison Project (Fish‐MIP) to analyze responses of marine animal biomass in all major ocean basins to contrasting climate change scenarios. Under a high emissions scenario (RCP8.5), total marine animal biomass declined by an ensemble mean of 15%–30% (±12%–17%) in the North and South Atlantic and Pacific, and the Indian Ocean by 2100, whereas polar ocean basins experienced a 20%–80% (±35%–200%) increase. Uncertainty and model disagreement were greatest in the Arctic and smallest in the South Pacific Ocean. Projected changes were reduced under a low (RCP2.6) emissions scenario. Under RCP2.6 and RCP8.5, biomass projections were highly correlated with changes in net primary production and negatively correlated with projected sea surface temperature increases across all ocean basins except the polar oceans. Ecosystem structure was projected to shift as animal biomass concentrated in different size‐classes across ocean basins and emissions scenarios. We highlight that climate change mitigation measures could moderate the impacts on marine animal biomass by reducing biomass declines in the Pacific, Atlantic, and Indian Ocean basins. The range of individual model projections emphasizes the importance of using an ensemble approach in assessing uncertainty of future change.

Effect of natural and synthetic Brassinosteroids on strawberry immune response against Colletotrichum acutatum - R. N. Furio; P. L. Albornoz; Y. Coll; G. M. Martínez Zamora; S. M. Salazar; G. G. Martos; J. C. Díaz Ricci (European Journal of Plant Pathology, 2019)

Drought variability and change across the Iberian Peninsula - J.R. Coll; E. Aguilar; L. Ashcroft (Theoretical and Applied Climatology, 2017)

Regional-Scale Differences in Eutrophication Effects on Eelgrass-Associated (Zostera marina) Macrofauna - Allison L. Schmidt; Marta Coll; Heike K. Lotze (Estuaries and Coasts, 2017)

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Flower structure and developmental stages of the capitulum of Smallanthus sonchifolius (Asteraceae): reproductive implications - M. S. Ibañez; M. I. Mercado; M. V. Coll Aráoz; M. L. Zannier; A. Grau; G. I. Ponessa (Journal of Plant Research, 2017)

Repeated exposure to vicarious pain alters electrocortical processing of pain expressions - Michel-Pierre Coll; Mathieu Grégoire; Kenneth M. Prkachin; Philip L. Jackson (Experimental Brain Research, 2016)

Homogenization and analysis of an expanded long‐term monthly rainfall network for the Island of Ireland (1850–2010) - S. Noone; C. Murphy; J. Coll; T. Matthews; D. Mullan; R. L. Wilby; S. Walsh (International Journal of Climatology, 2016)
Long‐term precipitation series are critical for understanding emerging changes to the hydrological cycle. To this end we construct a homogenized Island of Ireland Precipitation ( IIP ) network comprising 25 stations and a composite series covering the period 1850–2010, providing the second‐longest regional precipitation archive in the British‐Irish Isles. We expand the existing catalogue of long‐term precipitation records for the island by recovering archived data for an additional eight stations. Following bridging and updating of stations HOMogenisation softwarE in R ( HOMER ) homogenization software is used to detect breaks using pairwise and joint detection. A total of 25 breakpoints are detected across 14 stations, and the majority (20) are corroborated by metadata. Assessment of variability and change in homogenized and extended precipitation records reveal positive (winter) and negative (summer) trends. Trends in records covering the typical period of digitization (1941 onwards) are not always representative of longer records. Furthermore, trends in post‐homogenization series change magnitude and even direction at some stations. While cautionary flags are raised for some series, confidence in the derived network is high given attention paid to metadata, coherence of behaviour across the network and consistency of findings with other long‐term climatic series such as England and Wales precipitation. As far as we are aware, this work represents the first application of HOMER to a long‐term precipitation network and bodes well for use in other regions. It is expected that the homogenized IIP network will find wider utility in benchmarking and supporting climate services across the Island of Ireland, a sentinel location in the North Atlantic.

Both Volatiles and Cuticular Plant Compounds Determine Oviposition of the Willow Sawfly Nematus oligospilus on Leaves of Salix spp. (Salicaceae) - Celina L. Braccini; Andrea S. Vega; M. Victoria Coll Aráoz; Peter E. Teal; Teresa Cerrillo; Jorge A. Zavala; Patricia C. Fernandez (Journal of Chemical Ecology, 2015)

Growth and yield of mixed versus pure stands of Scots pine (Pinus sylvestris L.) and European beech (Fagus sylvatica L.) analysed along a productivity gradient through Europe - H. Pretzsch; M. del Río; Ch. Ammer; A. Avdagic; I. Barbeito; K. Bielak; G. Brazaitis; L. Coll; G. Dirnberger; L. Drössler; M. Fabrika; D. I. Forrester; et al. (European Journal of Forest Research, 2015)

Exploring the links between forest transition and landscape changes in the Mediterranean. Does forest recovery really lead to better landscape quality? - Joan Marull; Iago Otero; Constantí Stefanescu; Enric Tello; Marta Miralles; Francesc Coll; Manel Pons; Giovanna L. Diana (Agroforestry Systems, 2015)

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

The global ocean is an ecosystem: simulating marine life and fisheries - Villy Christensen; Marta Coll; Joe Buszowski; William W. L. Cheung; Thomas Frölicher; Jeroen Steenbeek; Charles A. Stock; Reg A. Watson; Carl J. Walters (Global Ecology and Biogeography, 2015)
Aim There has been considerable effort allocated to understanding the impact of climate change on our physical environment, but comparatively little to how life on Earth and ecosystem services will be affected. Therefore, we have developed a spatial–temporal food web model of the global ocean, spanning from primary producers through to top predators and fisheries. Through this, we aim to evaluate how alternative management actions may impact the supply of seafood for future generations. Location Global ocean. Methods We developed a modelling complex to initially predict the combined impact of environmental parameters and fisheries on global seafood production, and initially evaluated the model's performance through hindcasting. The modelling complex has a food web model as core, obtains environmental productivity from a biogeochemical model and assigns global fishing effort spatially. We tuned model parameters based on M arkov chain random walk stock reduction analysis, fitting the model to historic catches. We evaluated the goodness‐of‐fit of the model to data for major functional groups, by spatial management units and globally. Results This model is the most detailed ever constructed of global fisheries, and it was able to replicate broad patterns of historic fisheries catches with best agreement for the total catches and good agreement for species groups, with more variation at the regional level. Main conclusions We have developed a modelling complex that can be used for evaluating the combined impact of fisheries and climate change on upper‐trophic level organisms in the global ocean, including invertebrates, fish and other large vertebrates. The model provides an important step that will allow global‐scale evaluation of how alternative fisheries management measures can be used for mitigation of climate change.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Risk of intrauterine growth restriction among HIV-infected pregnant women: a cohort study - M. López; M. Palacio; A. Goncé; S. Hernàndez; F. J. Barranco; L. García; M. Loncà; J. O. Coll; E. Gratacós; F. Figueras (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Global in scope and regionally rich: an IndiSeas workshop helps shape the future of marine ecosystem indicators - Yunne-Jai Shin; Alida Bundy; Lynne J. Shannon; Julia L. Blanchard; Ratana Chuenpagdee; Marta Coll; Ben Knight; Christopher Lynam; Gerjan Piet; Anthony J. Richardson (Reviews in Fish Biology and Fisheries, 2012)

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR - L. Selva; P. Ciruela; C. Esteva; M. F. Sevilla; G. Codina; S. Hernandez; F. Moraga; J. J. García-García; A. Planes; F. Coll; I. Jordan; N. Cardeñosa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Valuing acorn dispersal and resprouting capacity ecological functions to ensure Mediterranean forest resilience after fire - C. Puerta-Piñero; L. Brotons; L. Coll; J. R. González-Olabarría (European Journal of Forest Research, 2012)

The Mediterranean Sea under siege: spatial overlap between marine biodiversity, cumulative threats and marine reserves - Marta Coll; Chiara Piroddi; Camille Albouy; Frida Ben Rais Lasram; William W. L. Cheung; Villy Christensen; Vasiliki S. Karpouzi; François Guilhaumon; David Mouillot; Michelle Paleczny; Maria Lourdes Palomares; Jeroen Steenbeek; et al. (Global Ecology and Biogeography, 2012)
Aim A large body of knowledge exists on individual anthropogenic threats that have an impact on marine biodiversity in the Mediterranean Sea, although we know little about how these threats accumulate and interact to affect marine species and ecosystems. In this context, we aimed to identify the main areas where the interaction between marine biodiversity and threats is more pronounced and to assess their spatial overlap with current marine protected areas in the Mediterranean. Location Mediterranean Sea. Methods We first identified areas of high biodiversity of marine mammals, marine turtles, seabirds, fishes and commercial or well‐documented invertebrates. We mapped potential areas of high threat where multiple threats are occurring simultaneously. Finally we quantified the areas of conservation concern for biodiversity by looking at the spatial overlap between high biodiversity and high cumulative threats, and we assessed the overlap with protected areas. Results Our results show that areas with high marine biodiversity in the Mediterranean Sea are mainly located along the central and north shores, with lower values in the south‐eastern regions. Areas of potential high cumulative threats are widespread in both the western and eastern basins, with fewer areas located in the south‐eastern region. The interaction between areas of high biodiversity and threats for invertebrates, fishes and large animals in general (including large fishes, marine mammals, marine turtles and seabirds) is concentrated in the coastal areas of Spain, Gulf of Lions, north‐eastern Ligurian Sea, Adriatic Sea, Aegean Sea, south‐eastern Turkey and regions surrounding the Nile Delta and north‐west African coasts. Areas of concern are larger for marine mammal and seabird species. Main conclusions These areas may represent good candidates for further research, management and protection activities, since there is only a maximum 2% overlap between existing marine protected areas (which cover 5% of the Mediterranean Sea) and our predicted areas of conservation concern for biodiversity.

Hyperspectral indices for detecting changes in canopy reflectance as a result of underground natural gas leakage - M. F. Noomen; K. L. Smith; J. J. Colls; M. D. Steven; A. K. Skidmore; F. D. Van Der Meer (International Journal of Remote Sensing, 2008)

The Systemic Absorption of Etoposide after Intravaginal Administration in Patients with Cervical Intraepithelial Lesions Associated with Human Papillomavirus Infection - P. García-López; M. Coll; E. Cervera; L. Reyes-Vermot; M. A. Torres; G. Ábrego-Pérez; A. I. Hernández-Pájaro; G. Castañeda-Hernandez; A. Mohar-Betancourt; A. Meneses (Pharmaceutical Research, 2006)

A Facility to Investigate Effects of Elevated Soil Gas Concentration on Vegetation - K. L. Smith; J. J. COLLS; M. D. Steven (Water, Air, & Soil Pollution, 2005)

Detection of QTL affecting fatty acid composition in the pig - Alex Clop; Cristina Ovilo; Miguel Perez-Enciso; Albert Cercos; Anna Tomas; Ana Fernandez; Agustina Coll; Josep M. Folch; Carmen Barragan; Isabel Diaz; Maria A. Oliver; Luis Varona; et al. (Mammalian Genome, 2003)

Fluid Motion Effect on Metal Toxicity in Bufo arenarum Embryos - J. Herkovits; L. Corró; C. Pérez-Coll; O. Domínguez (Bulletin of Environmental Contamination and Toxicology, 2002)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Abstracts of lectures presented at symposium on plant protection and the environment: Pesticides and their alternatives - Claude L. Alabouvette; Ilan Chet; Jaacov Katan; Bruce D. Hammock; George Kamita; Bora Inceoglu; Qihong Huang; Jane Townson; David Evans; Baruch Rubin; Deborah K. Letourneau; Moshe Coll (Phytoparasitica, 2000)

Effect of nutrient enrichment on the complementary (secondary) metabolite composition of the soft coral Sarcophyton ehrenbergi (Cnidaria: Octocorallia: Alcyonaceae) of the Great Barrier Reef - B. G. Fleury; J.C. Coll; E. Tentori; S. Duquesne; L. Figueiredo (Marine Biology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)